DISTRIBUSI PENDAPATAN PETANI KELAPA SAWIT POLA SWADAYA DI DESA RIMPIAN KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Adil, Posma; Eliza, Eliza; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study were 1) to analyze the structure of the income of farmers palm pattern swadaya 2) To analyze the oil palm farmers income distribution pattern of self-reliance. This research was conducted in the village of Lubuk Batu Jaya Rimpian District of Indragiri Hulu. The research method used is survey method with a sample of the study were 60 oil palm growers pattern of non-respondents. Analysis of the data for this study by calculating the income structure and income distribution. Revenue oil palm farmers in the village of Rimpian sourced from farms in the amount of Rp 41,323,366 per year and from non-agricultural sources of Rp 2,902,000 per year. The average total income of the entire oil palm farmers in the village self-supporting patterns Rimpian reached Rp 44,225,366 per year with an average of Rp 3,685,447 per month. Based on the data obtained Gini index ratio of 0.05 indicates a low inequality because it is under 0.3 Gini Index Ratio. Lorenz curve is formed from the value of approaching the perfect evenness. Thus, the distribution of income in the village oil palm farmers Rimpian not limp or have been fairly evenly evidenced by the second line of the Lorenz curve approaches the diagonal line (line equalization).Keywords: Income distribution, oil palm, pattern swadaya